THE ANALYSIS STUDY OF INTERPREGNANCY WEIGHT CHANGE AND HYPERTENSION DURING PREGNANCY: A COMPREHENSIVE SYSTEMATIC REVIEW - Wijaya, Vennylia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: The established correlation between high pre-pregnancy body mass index (BMI) and maternal and neonatal complications underscores the urgent need for comprehensive weight management strategies among expectant mother. The aim of this study is to investigate existing evidence on the relationship between interpregnancy weight change and hypertensive disorders during subsequent pregnancies based on literatures of the last 10 years. Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. It excluded editorials, reviews from the same journal, and submissions without a DOI. PubMed, SagePub, SpringerLink, and Google Scholar were utilized as literature sources. Result: Initially retrieving 500 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) eight relevant papers were selected after three rounds of screening for full-text analysis. These papers were thoroughly examined to assess the effect of interpregnancy weight change on hypertensive disorders during pregnancy. Conclusion: Interpregnancy weight gain is linked to a heightened risk of hypertensive disorders during pregnancy. By addressing weight-related factors between pregnancies, healthcare providers can significantly improve maternal health outcomes in subsequent pregnancies.